Direct hydrothermal synthesis of highly ordered Sn-SBA-15 mesoporous materials - Shah, Pallavi; Ramaswamy, Arumugamangalam V.; Ramaswamy, Veda (Chemistry Letters, 2006)
Well-ordered Sn4+-incorporated mesoporous silica SBA-15 samples have been synthesized from tetraethyl orthosilicate (TEOS) and SnCl4 (Si/Sn = 114-15) using nonionic surfactants under a slightly higher pH medium (optimum H2O to HCl molar ratio) and characterized by XRD (an increase in lattice parameter), TEM (no SnO2 species) and UV-vis spectral (absorption at 211 nm) techniques to show that Sn4+ ions are in tetrahedral coordination in Sn-SBA-15.

Immobilization of Ntn hydrolases on APTES fuctionalized SBA-15 - Shah, Pallavi; Sridevi, N.; Prabhune, Asmita; Ramaswamy, Veda (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
APTES Functionalized mesoporous silica SBA-15 molecular sieves have been prepared and used for immobilization of Penicillin G acylase. Physico chemical characterization was done by nitrogen adsorption, powder XRD and TEM methods to understand the nature of immobilized PGA enzyme. XRD data indicate a good mesoscopic order. The characteristic hexagonal features of SBA-15 were maintained in PGA immobilized SBA-15 samples. Incorporation of PGA does not affect the original pore structure of the parent SBA-15. The adsorption of PGA on SBA-15 from buffered solutions with a pH value, 7.8 has been studied as a model protein adsorption system. The maximum activity of the immobilized enzyme was observed at pH 7.8, slightly below the isoelectric point of the enzyme. The loading capacity of immobilized PGA is 34 mg protein per 0.5 g of SBA-15. The stability of Penicillin G acylase was enhanced by the physical entrapment in SBA-15.

Structural features of Penicillin acylase adsorption on APTES functionalized SBA-15 - Shah, Pallavi; Sridevi, N.; Prabhune, Asmita; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2008)
The immobilization of Penicillin acylase (PGA) enzyme (which belongs to the Ntn hydrolase super family) into the amino-functionalized SBA-15 mesoporous molecular sieve is carried out to see the effect of silica as a host matrix on the enzyme kinetics. Physicochemical characterization by nitrogen adsorption, powder XRD and TEM methods indicate that the characteristic hexagonal features and the original pore structure of the parent SBA-15 is retained even after the incorporation of PGA. The adsorption of PGA on SBA15 shows a dependence on the pore volume and the composition of the adsorbent. The maximum loading of the enzyme was observed at pH 7.8, slightly below the isoelectric point of the enzyme. The loading capacity of immobilized PGA is 34 mg protein per 0.5 g of SBA-15. The trapped enzyme is more stable than the soluble form to temperature and pH environments and retained 73% of its activity after immobilization. This enhanced stability is attributed to the protective nature of the cage itself and to the rigidity of the SiO(2) matrix, which reduces the freedom of peptide-chain refolding of molecular motions that occur in denaturation processes. The strength of binding is very strong; however, the activity of the immobilized enzyme is then simply restored with very little leakage of enzyme from the support. An important feature of the immobilized PGA enzyme is the excellent reusability without significant loss in activity, which indicates potentially exciting industrial/biomedical application of this support. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Penicillin G acylase; PGA immobilized SBA-15; pH and temperatures stability; SBA-15

Synthesis, characterization and catalytic activity of Sn-SBA-15 mesoporous molecular sieves - Ramaswamy, Veda; Shah, Pallavi; Lazar, Karoly; Ramaswamy, A. V. (Catalysis Surveys from Asia, 2008)
Our recent reports on the synthesis of Sn-incorporated mesoporous SBA-15 materials have been reviewed. The preparation of the samples with different Si/Sn ratios followed two procedures, the first is the post-synthesis modification of SBA-15 by impregnation with Sn chloride or acetate, and the second is the direct method in which Sn chloride was introduced in to Si precursor along with amphiphilic triblock copolymer, while varying the ratio of the synthesis gel. Detailed characterization of the Sn-SBA-15 samples by a variety of techniques shows how the synthesis procedures influence the properties of the samples that reflect on the differences in (a) the structural features, (b) morphology and textural properties, such as the pore characteristics, (c) the possible location of Sn4+ ions in the meso silica structure and their reducibility, (d) the nature of the Sn species and their the coordination sphere and (e) the acid-base characteristics. We developed a possible model for the localization of Sn species in SBA-15 pore structure for different conditions of preparation. This report includes our investigations on the catalytic properties of these Sn-SBA-15 samples in 3 industrially important reactions, viz., trans-esterification of diethyl malonate, synthesis of nopol by Prins condensation of beta-pinene with para-formaldehyde and the epoxidation of norbornene. In each of this reaction, while demonstrating the catalytic role of Sn species, we show that the requirement of the type and the environment of Sn species are different for these reactions.
Keywords: mesoporous materials; Properties of Sn-SBA-15; Sn-containing SBA-15; Sn-SBA-15 catalysts; Synthesis of Sn-SBA-15

Thermal stability of mesoporous SBA-15 and Sn-SBA-15 molecular sieves: an in situ HTXRD study - Shah, Pallavi; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2008)
Highly ordered SBA-15 and Sn-SBA-15 mesoporous molecular sieves with Si/Sn = 80, 60, 40 and 10 have been prepared through direct synthesis route under milder acidic conditions, which were used for the in situ high temperature X-ray diffraction (HTXRD) studies in the temperature range 298-1573 K for the first time in the literature. SBA-15 is found to be thermally stable up to 1473 K and appearance of alpha-cristobalite was observed at 1573 K also supported by the thermogravimetric (TG) data. A strong negative thermal expansion was observed on heating from 298 to 1573 K (alpha(a) = -4.3 x 10(-6) K-1). Sit containing samples (Si/Sn = 80 and 60) showed a positive thermal expansion (6.75 x 10(-6) K-1 and 9.04 x 10(-6) K-1, respectively). On the other hand, the samples with Si/Sn = 40 and 10 showed a strong negative thermal expansion (-4.12 x 10(-6) K-1 and -7.56 x 10(-6) K-1) similar to SBA-15. The linear thermal expansion coefficient varied in the order: Si/Sn = 60 > 80 > 40 > 0 > 10. Sn4+ ions exhibit both tetrahedral and octahedral coordination depending upon the location of these ions either on the walls of the silica (Si/Sn = 80 and 60) or in the corona region of the structure (Si/Sn = 40 and 10), respectively. The thermal decomposition of the samples (TG data) is correlated to the thermal expansion behavior (HTXRD data). The decomposition behavior of template ions located within the pores is strongly influenced by the presence of Sn in the framework and a `soft' interaction probably exists between the template ions and the Sn sites. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: HTXRD studies; phase transitions; Sn-SBA-15; TG data; Thermal expansion

Doping-induced microstructural, textural and optical properties of In2Ti1-xVxO5+delta semiconductors and their role in the photocatalytic splitting of water - Shah, Pallavi; Bhange, Deu S.; Deshpande, Aparna; Kulkarni, Mukund S.; Gupta, Narendra M. (Materials Chemistry and Physics, 2009)
The physicochemical properties of V-doped indium titanates (In2Ti1-xVxO5-delta, 0.0 <= x <= 0.2) were investigated by using XPS, powder XRD, UV-vis, SEM and luminescence spectroscopy techniques. The Rietveld refinement of XRD data revealed that even though the V-containing samples were isostructural with In2TiO5 (orthorhombic space group Pnma), a systematic x-dependent variation was noticeable in the Ti-O bond lengths in [TiO6] octahedral units, cell parameters and in the value of delta. XPS results confirmed the coexistence of V5+ and V4+ states, leading thereby to an enhancement in oxygen non-stoichiometry in the doped samples. A loading-dependent progressive shift from 400 to 750 nm was also observed in the onset of the absorption edge, indicating a significant narrowing of the band gap. Furthermore, the samples with higher V-content were comprised of the grain clusters having larger size and an irregular shape. The UV-vis. photoluminescence and thermoluminescence studies indicate that the doping-induced lattice defects may give rise to certain closely spaced acceptor/donor energy levels in between the band gap of host matrix. The indium titanates are found to serve as stable photocatalysts for water splitting under visible light, where oxygen was the major reaction product. The role of microstructural and morphological properties in the photocatalytic activity is discussed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: In2Ti1-xVxO5+delta photocatalysts; Luminescence spectroscopy; Microstructure; Optical properties; Structure-activity relationship; water splitting

Interfacial and physico-chemical properties of polymer-supported CdS center dot ZnS nanocomposites and their role in the visible-light mediated photocatalytic splitting of water - Deshpande, Aparna; Shah, Pallavi; Gholap, Ramkrishna S.; Gupta, Narendra M. (Journal of Colloid and Interface Science, 2009)
Nano-composite CdS center dot ZnS moieties coated over polyester strip were found to exhibit better visible-light-mediated photo-activity for splitting of water, as compared to corresponding pure CdS or ZnS containing coupons. This increase in activity depended upon the mol ratio of the two component sulphides in a particular sample. HRTEM experiments revealed the presence of 1-3 nm size CdS particles embedded over larger size ZnS clusters, the composite samples thus functioning as a highly dispersed guest-host system. In the case of CdS and ZnS dispersed individually over polyester, average crystallite size was found to be around 5 and 15 rim, respectively. A blue shift was observed in the UV-vis absorption spectrum of US oil addition of ZnS, in conformation with the quantum size effects. Powder XRD, electron diffraction and XPS Studies showed that the nanocomposites were comprised of the face-centered cubic (alpha) phases of both US and ZnS in a close contact with each other. At the same time, certain solid solution phases, i.e. Cd(1-x)Zn(x)S. were generated at the interfaces of these two semiconductors. Our Study demonstrates that the increase in the number of reaction sites due to smaller size of US particles and the micro-structural properties associated with the nanostructured US or CdS/ZnS interfaces may together play a vital role in the augmented catalytic activity of CdS center dot ZnS composite photocatalysts. (c) 2009 Elsevier Inc. All rights reserved.
Keywords: CdS center dot ZnS nanocomposites; Photocatalytic activity; Role of microstructural properties; Splitting of water